Pregnant Women's Knowledge About Anemia - Yuningsih (AACENDIKIA: Journal of Nursing, 2024)
Anemia in pregnant women is a condition characterized by hemoglobin levels below normal limits, which is less than 11 g/dL in the first and third trimesters, and less than 10.5 g/dL in the second trimester. This condition can increase the risk of pregnancy and childbirth complications. Pregnant women's knowledge about anemia is an important factor in efforts to prevent and treat anemia during pregnancy. This study aims to describe the level of knowledge of pregnant women about anemia in the Kelapa Dua Health Center work area, Tangerang Regency. The research method used was an analytical survey with a cross-sectional study approach. The study sample consisted of 20 pregnant women selected based on predetermined inclusion criteria. Data were collected through a questionnaire containing questions related to knowledge about anemia and hemoglobin level examination. The results showed that the majority of respondents were under 20 years old (65%) and had a bachelor's degree (55%). Based on the results of data analysis, 75% of pregnant women had sufficient knowledge about anemia, while 25% had insufficient knowledge. The prevalence of anemia in this study was 15%, with 3 out of 20 pregnant women experiencing anemia. Statistical analysis shows a significant relationship between the level of knowledge of pregnant women and the incidence of anemia (p-value <0.01). So it is concluded that the level of knowledge of pregnant women about anemia plays an important role in preventing and reducing the risk of anemia during pregnancy.